Levels of Proximate Compositions and Minerals (Na, K, Ca, Mg, Cu, and Zn) Present in Eucalyptus (Eucalyptus globulus) and Gingerbread Plum (Noecarya macrophylla) Leaves Collected from Sokoto Town - Sarkingobir, Yusuf; Sulaiman, Bello (Asian Journal of Science, Technology, Engineering, and Art, 2024)
Sokoto state is been challenged with diverse array of problems such as food insecurity, malnutrition, poor healthcare. Thus, the need to search for locally available plant materials is intensified. The objective of this work was to conduct a phytochemical, proximate and Na, K, Ca, Mg, Cu, Zn (minerals) analysis of eucalyptus (Eucalyptus globulus) and gingerbread plum (Noecarya macrophylla) leaves using standard methods and materials of analytical grade. The proximate results revealed moisture of (7.10 ± 09), (7.73 ±0.3) ash (14.76 ± 0.2) (12.85 ± 0.11), crude lipid (1.38± 0.007) (1.46 ±0.02), crude fibre (2.42 ± 0.03) (2.54 ± 0.03), crude protein (5.66 ± 0.04) (7.3 ± 0.006), carbohydrates (68. 68 ± 0.31) (68.12 ± 0.23) for gingerbread plum and eucalyptus respectively. The minerals in gingerbread plum and eucalyptus respectively are as follows; zinc (0.59± 0.06 ppm).4 ± (0.005 ppm), calcium (11.38 ± 0.6 ppm) (19.48 ± 0.53 ppm), potassium (7.21 ± 1.2 ppm) (5.10 ± 0.93 ppm), copper (0.51 ± 0.007 ppm) (0.19 ± 0.04 ppm), magnesium (3.74 ± 0.41 ppm), (10.9 ± 93 ppm), sodium (7.65 ± 0.63 ppm) (12.21 ± 0.32 ppm). Phytochemicals determined include, alkaloids, saponins, tannins, phenols, and phytate. The results have revealed that, the two plants are rich in proximate, phytochemicals and minerals and can be useful for consumption.